Improving Listening Skills Towards Music and Video in Millenial Era - Tia Safira; Julaila Sari; Raja Radhiah; Tia Safira (English Instruction, 2020)
Proficiency in English is also measured by listening skills. If we have good listening skills, communication using English will also be smoother. People who have the ability to listen are now a plus in itself. Basically, there are four important aspects in English that we must always understand, one of which is listening. Every person in understanding the four concepts always has a different level of difficulty. The obstacles that often occur in understanding this are not entirely our fault, but because of the selection and use of learning methods that are less attractive. Or the methods we use are too monotonous and boring, so we don't get the real essence of learning English. Therefore, we need the most effective learning methods. In this millennial era, the most alternative way to improve the quality of listening is by listening to music and watching video. Music is an easy habit, when we listen to music we don't need to spend a lot of time because music can be taken anywhere. We can play songs in the car, kitchen and bedroom. By choosing the music we like, we can listen to the same material over and over again without getting bored. Watching English videos has become a recommendation for many people. To improve Listening ability, it is considered effective because the three-dimensional media is easily accessible, not boring, and has a unique appeal.